Cancer survival in China, 2003–2005: A population‐based study. Issue 8 (3rd October 2014) - Zeng, Hongmei; Zheng, Rongshou; Guo, Yuming; Zhang, Siwei; Zou, Xiaonong; Wang, Ning; Zhang, Limei; Tang, Jingao; Chen, Jianguo; Wei, Kuangrong; Huang, Suqin; Wang, Jian; et al.
<x xml:space="preserve">Abstract</x> Limited population‐based cancer registry data available in China until now has hampered efforts to inform cancer control policy. Following extensive efforts to improve the systematic cancer surveillance in this country, we report on the largest pooled analysis of cancer survival data in China to date. Of 21 population‐based cancer registries, data from 17 registries (n = 138, 852 cancer records) were included in the final analysis. Cases were diagnosed in 2003–2005 and followed until the end of 2010. Age‐standardized relative survival was calculated using region‐specific life tables for all cancers combined and 26 individual cancers. Estimates were further stratified by sex and geographical area. The age‐standardized 5‐year relative survival for all cancers was 30.9% (95% confidence intervals: 30.6%‐31.2%). Female breast cancer had high survival (73.0%) followed by cancers of the colorectum (47.2%), stomach (27.4%), esophagus (20.9%), with lung and liver cancer having poor survival (16.1% and 10.1%), respectively. Survival for women was generally higher than for men. Survival for rural patients was about half that of their urban counterparts for all cancers combined (21.8% vs. 39.5%); the pattern was similar for individual major cancers except esophageal cancer. The poor population survival rates in China emphasize the urgent need for government policy changes and investment to improve health services. While the causes for the striking urban‐rural disparities observed are not fully understood, increasing access of health service in rural areas and providing basic health‐care to the disadvantaged populations will be essential for reducing this disparity in the future.